Occupational Therapy Students’ Perceptions of the Role of Robots in the Care for Older People Living in the Community - Sławomir Tobis; Mirosława Cylkowska-Nowak; Katarzyna Wieczorowska-Tobis; Mariola Pawlaczyk; Aleksandra Suwalska (Occupational Therapy International)
Background. The question arises how recent developments in robotics can contribute to the care for older people. The study is part of the EU-funded ENRICHME project. Objectives of Study. The aim of the study was to investigate opinions of occupational therapy students (OTS), as future professional caregivers, on the use of robots in care for older people. Methods. It included 26 OTS from Poznan University of Medical Sciences. To collect data, the Users’ Needs, Requirements, and Abilities Questionnaire (UNRAQ) was developed. Findings. OTS perceived the robot as “a useful device” and “an assistant” rather than “a companion” (p<0.01). In their opinion, the most important functions of the robot were related to health aspects (emergency alarms, health parameters monitoring, physical activity and memory training, and reminders about medication, drinks, etc.), scored positively by 23–26 OTS. Functions such as mood detection, encouraging to contact with friends, and monitoring of food consumption were accepted by 16-17 OTS. Two statements concerning social functions (accompanying in everyday activities and decreasing the sense of loneliness) were rated positively by less the than half of the participants. Limitations and Recommendations for Further Research. A module concerning technology use, including robotics, should constitute an important part of the curricula of both academic and continuous education of OTS.